Kajian Kesiapan Tata Kelola Pemerintahan Daerah pada Pelaksanaan KPBU Availability Payment (AP) - Nababan, Henro Nababan (Civil Infrastructure Engineering and Architectural Design, 2024)
The current Local Government is currently focusing on sustainable infrastructure development to provide quality infrastructure facilities to the community. Responding to this condition, the Local Government really needs clear funding sources and well-targeted infrastructure projects. Public Private Partnerships (PPP) is an infrastructure financing innovation that can be implemented by Local Governments, where one of the investment return schemes is Availability Payment. However, based on PPP Books for 2010-2022, only 1 project was successful (8.3%). Many projects are unsuccessful due to the lack of PPP nodes, clear regulations and support from stakeholders, which is the Local Government Governance itself. This research began by conducting a review of several literatures, then conducting interviews to adapt this governance to the characteristics of local government in Indonesia. Furthermore, the indicators that have been obtained will later become a reference for assessing the readiness of Local Government Governance in implementing the PPP Availability Payment. And the results of the analysis that there are 5 indicators of Local Government Governance readiness in the implementation of the Availability Payment, Government Maturity, Social Policy Framework, Institutional Capacity, Legal & Regulatory Environment, and Project Delivery. Furthermore, the results of the assessment show that the Madiun Regency government is more prepared than the Bandung City government in implementing the Availability Payment PPP project in the Public Street Lighting sector.